1999
DOI: 10.1074/jbc.274.26.18492
|View full text |Cite
|
Sign up to set email alerts
|

Methylglyoxal Modification of Protein

Abstract: Methylglyoxal (MG), an endogenous metabolite that increases in diabetes and is a common intermediate in the Maillard reaction (glycation), reacts with proteins and forms advanced glycation end products. In the present study, we identify a novel MG-arginine adduct and also characterize the structure of a major fluorescent adduct. In addition, we describe the immunochemical study on the MG-arginine adducts using monoclonal antibody directed to MG-modified protein. On the other hand, as an immunochemical approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
144
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 341 publications
(147 citation statements)
references
References 41 publications
1
144
0
2
Order By: Relevance
“…Thus, it is conceivable that the frequent intake of dietary § Lin, J., Alt, A., Liersch, J., Reinhard, G. B., Brownlee AGE promotes a sustained low-grade inf lammatory state. In this sense, other markers of immune response such as cytokines and adhesion molecules are inducible by AGEs via reactive oxygen species production and nuclear factor B activation (7)(8)(9)(10)(11)(12)(13)(14)44), properties which are also exhibited by dietary AGEs (25). These reactive molecules (ranging between 12 and 22 million AGE units in a ''healthy meal''), which are ''seeding'' the systemic circulation regularly, could, together with hyperglycemia, contribute to the subtle inf lammatory state associated with diabetes (23,(41)(42)(43)45).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it is conceivable that the frequent intake of dietary § Lin, J., Alt, A., Liersch, J., Reinhard, G. B., Brownlee AGE promotes a sustained low-grade inf lammatory state. In this sense, other markers of immune response such as cytokines and adhesion molecules are inducible by AGEs via reactive oxygen species production and nuclear factor B activation (7)(8)(9)(10)(11)(12)(13)(14)44), properties which are also exhibited by dietary AGEs (25). These reactive molecules (ranging between 12 and 22 million AGE units in a ''healthy meal''), which are ''seeding'' the systemic circulation regularly, could, together with hyperglycemia, contribute to the subtle inf lammatory state associated with diabetes (23,(41)(42)(43)45).…”
Section: Discussionmentioning
confidence: 99%
“…Immunoreagents to MG derivatives and CML-like products, however, have presented invaluable means for animal and clinical correlations (10,11,24,25). It thus has been confirmed that two-thirds of orally absorbed dietary AGEs (Ϸ10% of the amount ingested) are retained in tissues in bioreactive forms (26,27).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…After TNF incubations (1.5 or 2.5 h), the cells were rinsed three times with ice-cold PBS buffer, and cell lysates were prepared in a 3-[(3-cholamidopropyl)dimethylammonio]-1-propanesulfonatecontaining cytosol extraction buffer (29). MG-derived AGEs were detected by Western blotting by using the mAb6B (19). To use the antibody sparingly, SDS-polyacrylamide gels were only run across a distance of 5 cm.…”
Section: Identification Of the Protein Spot As Glo1 By Matrix-assistementioning
confidence: 99%
“…Although the reaction with Cys is considered reversible, elevated concentrations of MG can lead to irreversible modifications of Lys and Arg residues through formation of advanced glycation end products (AGEs) (18). AGE formation is thought to contribute to several pathophysiological conditions, such as tissue damage after ischemia͞ reperfusion (19), to aging (20), and to the development of complications in diabetic patients such as blindness, neuropathy, and diabetic vascular diseases (21). vol͞vol), heat-inactivated newborn calf serum (5% vol͞vol), penicillin (100 units͞ml), streptomycin (0.1 mg͞ml), and Lglutamine (2 mM), at 37°C in a humidified incubator under a 5% CO 2 atmosphere.…”
mentioning
confidence: 99%